Design of Rhombus-Shaped Slot Patch Antenna for Wireless Communications - Saravanan, Manavalan; Rangachar, Madihally Janardhana Srinivasa (Journal of Computer Networks and Communications, 2019)
A single feed circularly polarized patch antenna is presented. The antenna consists of a rhombus-shaped slot incorporated in the radiating patch at its center. The antenna is designed to operate at 2.3 GHz band. The antenna achieves left-hand polarization or right-hand polarization based on the orientation of the slot in the radiating patch. The antenna parameters are synthesized using a high-frequency structure simulator and its characteristics are validated by the Agilent network analyzer (N9925A) and antenna test systems. The measured results obtained agree with simulated results and show that the antenna achieves −10 dB impedance bandwidth of 85 MHz (2.27 GHz–2.355 GHz) for left-hand polarization and 85 MHz (2.26 GHz–2.345 GHz) for right-hand polarization. The antenna gives a 3 dB axial ratio beamwidth of 95°(−35° ≤ AR ≤ 60°) for both left-hand polarization and right-hand polarization along with better 3 dB axial ratio bandwidth of 140° in the operating band. The antenna also achieves a good cross-polarization isolation of −17 dBic for both left-hand and right-hand polarization at its operating frequency. Hence, the antenna is best suited for modern wireless communication systems.